(untitled) (Ahkam: Jurnal Hukum Islam, 2017)
The article discussed about the dissemination of hoax news that contain hate speech. The method used in this article is library research because the case is actual cases. Hate speech based on information dan electronic transactions law is prohibibted and given a strict punishment for the perpetrators. The MUI has also forbid hate speech. Keywords: Hate Speech, UU ITE, MUI Pendahuluan